Optimization of the formulation of nutritional breads based on calcium carbonate and inulin - Salinas, Maria Victoria (2015)
The purpose of this work was to optimize nutritional wheat bread formulation based on calcium carbonate and inulin (In); and to study dough fermentation properties and bread quality. During fermentation, time (tf) and dough volume (Vmax) were analyzed. Specific volume (Vs), crust colour, moisture, texture and alveolus properties of crumb are studied. Dough with high In content experienced a fast although less expansion. Furthermore, calcium fortification decreased tf. Crust colour was dependent on inulin content. At 13g/100g In, the lowest dough Vmax but the highest Vs bread was obtained. Crumb firmness and chewiness increased with 6.5g/100g In although high level of prebiotic did not modify these parameters. At the same In quantity, an increase of calcium carbonate resulted on softer and more elastic crumbs. Crumb moisture, decreased with the increment of prebiotic. Without In and in the presence of Ca, crumbs presented low alveolus area. The highest Vs of 13g/100g In breads was due to the high number of alveolus with a large void area. Based on the response surface of multiples variables (moisture, cohesiveness, chewiness, Vs) was optimized using a desirability function; the optimum calcium-prebiotic fortified bread obtained was that one that contained 2.196g/kg Ca and 9.635g/100g In.